The level of satisfaction when using social media to express opinion / Erynnadiyah Nuraisyah Asharudin and Muhammad Hafiez Zulhakim Zailani - Asharudin, Erynnadiyah Nuraisyah; Zailani, Muhammad Hafiez Zulhakim (Faculty of Communication & Media Studies, 2023)
In this era, social media complements many aspects of our lives. It provides a variety of services to the public, including the ability to share thoughts and opinions on social media platforms such as Twitter, Facebook, and Instagram. This paper focuses on studying Malaysians' use of social media to express their opinions. This study applied the Users and Gratifications theory (UGT) as theories that explain how humans utilize or seek out particular media to satisfy their needs. This survey included 400 social media users, and the sample was acquired using Google Forms. The findings of this study depicted that people find satisfaction after voicing out their opinions on social media (M=3.03).